Income Patterns by Gender, Race and Marital Status in South Africa - Dunga, Hannah (Journal of Cultural Analysis and Social Change, 2026)
Income remains a fundamental determinant of individual and household well-being, shaping access to essential resources such as education, healthcare, housing, and social mobility. While philosophical debates may question the direct link between income and happiness, there is little dispute that a lack of income often results in heightened vulnerability, social exclusion, and limited agency. In this regard, income poverty not only affects material living standards but also undermines human dignity and increases susceptibility to exploitation and deprivation. Within the global development discourse, particularly as outlined in the United Nations Sustainable Development Goals (SDGs), poverty eradication is centrally linked to the promotion of inclusive economic growth and equitable access to income and wealth. Addressing poverty, however, requires an appreciation of its multidimensional nature and the structural inequalities that underpin it. This study investigates the determinants of household head labour salary in South Africa, utilizing cross-sectional data from the 2023 General Household Survey (GHS). Employing an Ordinary Least Squares (OLS) regression model on a sample of 10,883 households, the research aims to identify how demographic characteristics, marital status, and employment status influence individual earnings. The model explained 21.4% of the variance in labour salary, demonstrating a statistically significant overall fit. Key findings reveal that the age of the household head is a significant positive predictor of labour salary, consistent with human capital theory. Crucially, the analysis highlights persistent and substantial racial income disparities, with White and Indian/Asian household heads earning significantly more than their African and Coloured counterparts. For instance, White household heads earned 2.4 times more per month than African household heads, after controlling for other factors. A significant "marriage premium" was also identified, where legally married household heads earned more than those in other marital statuses. Interestingly, gender (being a female household head) did not show a statistically significant direct effect on labour salary in this model. These findings underscore the enduring impact of historical inequalities on South Africa's labour market, particularly along racial lines. The study recommends intensified policy interventions to address racial wage gaps, continued investment in human capital, and further research into the nuanced dynamics of gender and marital status on income to foster greater equity and economic well-being across the country.